Bilateral Total Hip Arthroplasty for Osteofibrous Dysplasia Assisted by CT‐Guided 3D Printing: A Case Report - Liwei Ying; Yuhang Zhang; Zhong Zhu; Zhongyi Chen; Jiajing Ye (Clinical Case Reports)
ABSTRACT Osteofibrous dysplasia with obvious deformities, persistent pain, functional problems, or pathological fractures usually requires surgical intervention. This report highlights that computed tomography‐based 3D printing preoperative planning can facilitate precise intraoperative positioning of the osteotomy plane and prosthesis stem design for complex bone deformities.